Trim the fat, gain the edge: lean supply chain activities for cost reduction and competitive advantage - Khawka, Zeyad Mustafa Hamed; Abd Rahman, Azmawani; Sidek, Shafie; Ahmed, Siti Azfanizam; Al-Hadeethi, Rami Hikmat Fouad (Elsevier, 2025)
This research investigates the interrelationships between lean supply chain activities (LSCA), supply chain cost reduction (SCCR), and competitive advantage (CA) among Iraqi food and beverage SMEs. This study assessed the moderating effect of information technology (IT) on the relationship between LSCA and SCCR, and developed new measurement scales for both LSCA and SCCR. Both resource-based view (RBV) and transaction cost economics (TCE) theories served as the underpinning theories of this study. Survey data collected from 375 SMEs were analyzed by Structural Equation Modelling (SEM) using SmartPLS4 software for hypothesis testing. The following key results were obtained: (1) the significant influence of LSCA and SCCR on CA; (2) the significant and positive influence of LSCA on SCCR; (3) SCCR as the mediator of the relationship; (4) IT capabilities as the moderator in the relationship between LSCA and SCCR. This study empirically proved the mediating role of SCCR and the moderating role of IT capabilities within the context of developing countries, as well as how LSCA can enhance CA, particularly for Iraqi food and beverage SMEs. This study presents valuable insights on LSCA, SCCR, and IT capabilities for enhanced CA, which would significantly benefit SME owners and managers. However, the cross-sectional design and sector-specific focus limit the generalizability of the findings, underscoring the need for future longitudinal and cross-sectoral research to enhance broader applicability and insight.